Construction of a co-expression network affecting intramuscular fat content and meat color redness based on transcriptome analysis - Wang, Binbin; Hou, Liming; Yang, Wen; Men, Xiaoming; Qi, Keke; Xu, Ziwei; Wu, Wangjun (Frontiers in Genetics, 2024)
Intramuscular fat content (IFC) and meat color are vital indicators of pork quality.A significant positive correlation between IFC and redness of meat color (a*CIE a* value) indicates that these two traits are likely to be regulated by shared molecular pathways. To identify candidate genes, hub genes, and signaling pathways that regulate these two traits, we measured the IFC and a*CIE a* value in 147 hybrid pigs, and we selected individuls with extreme phenotypes for transcriptome analysis. The results revealed 485 and 394 overlapping differentially expressed genes (DEGs), using the DESeq2, limma, and edgeR packages, affecting the IFC and a*CIE a* value, respectively. Weighted gene co-expression network analysis (WGCNA) identified four modules significantly correlated with the IFC and a*CIE a* value. Moreover, we integrated functional enrichment analysis results based on DEGs, GSEA, and WGCNA conditions to identify candidate genes, and identified 47 and 53 candidate genes affecting the IFC and a*CIE a* value, respectively. The protein-protein interaction (PPI) network analysis of candidate genes showed that 6 5 and 14 13 hub genes affect the IFC and a*CIE a* value, respectively. These genes mainly participate in various pathways related to lipid metabolism and redox reactions. Notably, four crucial hub genes (MYC, SOX9, CEBPB, and PPAGRC1A) were shared for these two traits. After functional annotation of these four hub genes, we hypothesized that the SOX9/CEBPB/PPARGC1A axis could co-regulate lipid metabolism and the myoglobin redox response. Further research on these hub genes, especially the SOX9/CEBPB/PPARGC1A axis, will help to understand the molecular mechanism of the co-regulation of the IFC and a*CIE a* value, which will provide a theoretical basis for improving pork quality.